Buried with their Buckles On: Clothed Burial at the Augustinian Friary, Cambridge. Issue 1 (2nd January 2022) - Cessford, Craig; Hall, Andrew; Mulder, Bram; Neil, Benjamin; Riddler, Ian; Wiles, Justin; ,; Cameron, Esther; Mould, Quita
Abstract : GIRDLE BUCKLES ASSOCIATED with several groups of burials at the later-medieval Augustinian friary in Cambridge indicate that clothed burial was common, with a much higher prevalence than usual for the period. The clothed burial was highly regularised, in terms of both the garments worn and the types of buckles used, and apparently limited to members of the Augustinian Order. The buckles were primarily supplied by the friary, rather than representing individual choices, and there is evidence that the girdles that individuals were buried with were those they used in life. These buckles functioned on several levels, as symbols of both corporate and personal identity. Discoveries at other English Augustinian friaries demonstrate specific typological parallels, indicating broader connections, networks and identities. Although buckles are common late-medieval items, those from the Cambridge Augustinian friary present a unique opportunity to contextualise their use by one segment of society.